Visual thinking in virtual environments: evaluating multidisciplinary interaction through drawing ideation in real-time remote co-design - Close, Alex; Field, Stephen; Teather, Robert (Frontiers in Virtual Reality, 2024)
This study investigated remote multidisciplinary sketching ideation across three systems: virtual reality (VR), tablet drawing, and uploading images of paper drawings. Though cumbersome, expressiveness and line control with drawing on paper was still noted to be important even in remote sketching, particularly by people experienced with this method. The tablet method was user-friendly, fostering effective collaborative understanding, especially in object-based ideation. Existing skills played a significant role in shaping collaborative perceptions. Despite challenges, VR exhibited promise in fostering creative expression and visualization in collaborative design workflows. Notably, it proved beneficial in early problem-solving stages where spatial and sensory considerations influenced structural decisions -potentially useful after general brainstorming and 2D sketching has established themes and objects. This research contributes to further understanding of VR's evolving role in design thinking, its synergy with other drawing methods in remote sketching collaboration, and the evolving landscape of diverse user needs in ideation processes.